2020
DOI: 10.3390/biom10071052
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin Ameliorates Impaired Bone Turnover by Inhibiting the Formation of Advanced Glycation End Products in Diabetic Osteoblasts and Osteoclasts

Abstract: Accumulating evidence demonstrates that the risk of osteoporotic fractures increases in patients with diabetes mellitus. Thus, diabetes-induced bone fragility has recently been recognized as a diabetic complication. As the fracture risk is independent of the reduction in bone mineral density, deterioration in bone quality may be the main cause of bone fragility. Coumarin exists naturally in many plants as phenylpropanoids and is present in tonka beans in significantly high concentrations. This study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Consistent with the microscopic results, our data on the quantification of the TRAP-positive multinucleated cells and TRAP activity showed significant differences between the analysed samples, with the Mg-PCL-CM exhibiting the highest levels. This result is in line with data reported by Lee et al [ 138 ] showing that CM promoted the formation of TRAP-positive multinucleated cells. Noteworthy, the co-presence of ZnO nanoparticles in the PCL-CM and PCL-CM coatings induced the most significant decrease in the mentioned two osteoclast-specific markers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the microscopic results, our data on the quantification of the TRAP-positive multinucleated cells and TRAP activity showed significant differences between the analysed samples, with the Mg-PCL-CM exhibiting the highest levels. This result is in line with data reported by Lee et al [ 138 ] showing that CM promoted the formation of TRAP-positive multinucleated cells. Noteworthy, the co-presence of ZnO nanoparticles in the PCL-CM and PCL-CM coatings induced the most significant decrease in the mentioned two osteoclast-specific markers.…”
Section: Discussionsupporting
confidence: 93%
“…Given the known anti-inflammatory activity of ZnO nanoparticles, studies have reported their dose-and size dependent effects on the inflammatory response of RAW 264.7 cells, with lower doses and smaller sized nanoparticles (30 nm) having the most beneficial effect [134][135][136]. Even though the anti-inflammatory activities of different CM compounds have been reported in several studies [50,[136][137][138][139] here, the extraction media obtained from the PCL-CM coated sample exhibited a more pronounced pro-inflammatory response close to the TCPS sample but two-fold lower than the bare alloy, a feasible explanation being the lower amount of CM released from the PCL-CM coating (15 µg mL −1 ) in comparison to the PLC-CM-ZnO coating (26 µg mL −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines were shown to induce the formation and activation of osteoclasts. Hyperglycemia also enhances RANKL expression [ 42 , 51 , 52 , 53 ]. Hyperglycemia was shown to directly alter the expression of osteoblast-related genes, such as osteocalcin, and to affect osteoblast differentiation in vitro [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are showed anti-ulcerogenic [ 5 ], antiparasitic [ 6 ], anti-inflammatory [ 7 , 8 , 9 , 10 , 11 ], and other properties [ 12 , 13 , 14 ]. They are also antioxidant [ 15 ], and anticoagulant compounds [ 16 , 17 , 18 , 19 ]. As such, they can be defined as new pharmaceutical candidates [ 20 ].…”
Section: Introductionmentioning
confidence: 99%